High‐Entropy Alloy‐Induced Metallic Glass Transformation: Challenges Posed by in situ Alloying via Additive Manufacturing. Issue 7 (13th September 2022) - Hadibeik, Sepide; Spieckermann, Florian; Nosko, Martin; Khodabakhshi, Farzad; Heydarzadeh Sohi, Mahmoud; Eckert, Jürgen
Abstract : In situ alloying and fabricating glassy structures through a layer‐by‐layer fashion approach are challenging but have high potential to develop novel‐graded materials. For the first time, this cost‐effective approach is applied to additive manufacturing (AM) of a Zr‐based bulk metallic glass (BMG) from high‐entropy alloys (HEAs). A newly developed composition of Zr40 Al20 Cu20 Ti20 is fabricated through laser powder bed fusion (LPBF). Process parameters are optimized within a wide range of laser power (50–200 W) as well as scanning speed (50–800 mm s −1 ). In all printed samples, microscopic and compositional examinations reveal no glass formation, but very fine grains and CuTi and AlTi nanocrystals. Some glassy transitions at the interfaces may be encouraged to occur with proper melting and mixing. However, the main reason for not obtaining a glassy matrix is the substantial proportion of unmelted Zr raw powder throughout the structure as spherical particles. Consequently, glass formation can be hindered by a considerable amount of compositional deviation. During LPBF, in situ alloying poses significant challenges to developing BMGs. Hence, the various stages of the process, including raw material specifications, laser settings, and process parameters, should be investigated further. Abstract : This article discusses the challenges induced by in situ alloying of Zr‐based bulk metallic glass manufactured by laser powder bed fusion (LPBF). Combining alloying and manufacturing can lead to the development of bulk metallic glasses. By focusing on reducing multiprocessing and final costs, significant progress can be made in the future.